Life of insects - Lau, Wei Hong (Universiti Putra Malaysia Press, 2013)
Insects have a simple life, and their main purpose in life is to reproduce. Unlike humans, they do not grow gradually. Insects undergo a series of transformations from egg, immature, pupae to adult. This process is called metamorphosis. Insects with complete metamorphosis will undergo all the four stages while insects with incomplete metamorphosis do not undergo the pupae stage. Insects like armyworms, butterflies, bees, beetles and flies undergo complete metamorphosis whereas termites, true bugs, dragonflies, cicadas and cockroaches do not.